Talent Identification & Selection: Mapping Literature Using Bibliometric Analysis - Nur Mustaqim Jamalludin; Syarizal Abdul Rahim; Norailis Ab Wahab; Anita Ismail (Academic International Dialogue (AID) Academy, 2024)
Purpose of the study: The purpose of the study was to discover the bibliometric profile of Talent Identification & Selection. This study's major goal is to investigate Talent Identification & Selection publications in the Scopus database. For example, the bibliometric profile of Talent Identification & Selection research, the increase of publications and average citations, and author collaboration across countries. 55 words Methodology: Bibliometric analysis performed with a package called Biblioshiny from R-Studio and VOSviewer 1.6.16. The current study applies bibliometric quantitative methods. In the foreground, on October 12, 2021, the screening process utilised looked for all references to "Talent Identification & Selection" in Scopus' "article title" and discovered 111 scholarly contributions from 1975 to 2021. 53 words. Main Findings: This finding corroborates bibliometric analysis as well as systematic content analysis. Researchers gathered bibliography data from the Scopus API for 111 English-language articles written by 301 published scholars, with a total of 1,590 total citations, which were obtained via the Scopus API. A total of 31 countries worked together to enhance the proportion of talent discovery and recruitment publications on the database. There were 178 affiliations between the universities or institutes where the authors served. However, out of 300 authors, only 17 co-authorships are connected. Based on the co-occurrence evaluation in the abstract field, 2869 words have been recognised from the complete documents. 103 words Novelty of the study: This study offers a global trend towards Talent Identification & Selection scientific production. It provides a comprehensive introduction of the study domain for researchers and practitioners interested in this topic, introducing readers to key studies, authors, universities, principles, and methods. Through its scope, goals, software package, and database, the current study tried to bridge knowledge gaps in the existing literature. 60 words